CDC influenza surveillance report no. 61, December 19, 1961 - Communicable Disease Center (U.S.) Epidemiology Branch. Surveillance Section.
"Scattered outbreaks of Influenza A2 (Asian) and Influenza B have been observed during 1961 in a number of countries throughout the world. Confirmed outbreaks of Asian influenza were reported from every continent except Antarctica. Influenza B was less ubiquitous, touching only Europe, North America and Asia with recognized outbreaks. Within the continental United States, Asian influenza made its mark early in 1961. At that time, outbreaks were reported from New York City, Stamford and New Haven, Connecticut. It was not prevalent elsewhere. No confirmed outbreaks of Asian influenza have been reported during the present season. In contrast, Influenza B is known to be etiologic in outbreaks in four States at the present time. These are Arizona, Florida, California and Colorado. Southern, Saskatchewan is also involved in an epidemic of Influenza B. Respiratory disease outbreaks are occurring with increasing frequency in the United States with the advent of the winter season. Several States are reporting outbreaks that would appear to be significantly more widespread than usual. These States are Oregon, Missouri, and Illinois. Epidemiologic, clinical, and laboratory studies are under way.Influenza vaccine production has been stepped up to meet the demands. The projected supply will be three times greater than that available last year. The recommendation of the Surgeon General to immunize the high risk groups remains most pertinent. Subcutaneous inoculation is the route of choice." - p. 3 I. Summary of information -- II. Epidemic reports: (A.) Asian inﬂuenza; (B.) Inﬂuenza B outbreaks-through October 1961 -- III. Inﬂuenza vaccine: (A.) Production; (B.) Utilization; (C.) Route of inoculation -- IV. Minor antigenic change -- V. Weekly pneumonia and influenza deaths December 19, 1961. This report was prepared in the Surveillance Section, Communicable Disease Center by Theodore C. Eickhoff, M. D., Chief, Influenza Surveillance Unit, with the Assistance of the Statistics Section, Robert E. Serfling, Ph.D., Chief. "For administrative use." - cover "Information contained in this report is a summary of data reported to CDC by State Health Departments, Epidemic Intelligence Service Officers, collaborating influenza diagnostic laboratories, and other pertinent sources. Much if it is preliminary in nature and is primarily in nature and is primarily intended for those involved in influenza control activities. It is understood that the contents of these report will not be released to the press, except by the Office of the Surgeon General, Public Health Service, U.S. Department of Health, Education and Welfare. State Health Officers, of course, will judge the advisability of releasing any information from their own state." - cover